Global warming potential of recycled aggregate concrete with supplementary cementitious materials. (15th July 2022) - Bennett, Bree; Visintin, Phillip; Xie, Tianyu
Abstract: Significant materials research has focused on the reduction of concrete demolition waste via reuse in recycled aggregate concrete (RAC) and the reduction in cement emissions through the use of blended binders incorporating supplementary cementitious materials (SCMs). This work is largely predicated on the assumption that the environmental impact of concrete will be reduced as a result of the inclusion of waste materials. That is, research focusing on the development of RAC mix designs has largely been conducted without parallel life-cycle assessment (LCA) to quantify the true environmental impact. Here, a LCA is conducted to quantify the global warming potential (GWP) of 590 mix designs derived from 42 studies that incorporate both recycled aggregate and a range of SCM types. The assessment considers both a volumetric functional unit and a combined volumetric and strength functional unit, the analysis also considers the absorption of atmospheric carbon via concrete carbonation both during and after service. For each type of SCM the range of predicted GWP is defined, and it is shown that substantial reductions in CO2 equivalent emissions arise from SCM addition. Further, the use of recycled aggregate is shown to be most environmentally beneficial in lower strength concretes in which it is possible to achieve the same mechanical properties as natural aggregate concrete controls. Highlights: Life-cycle assessment of 590 mix designs containing recycled aggregate and SCMs. Considers both a volumetric and a strength/volume functional unit. Analysis considers absorption of atmospheric carbon. The application of recycled aggregate is most beneficial for low strength concretes.